ADAMTS-7 Exhibits Elevated Expression in Cartilage of Osteonecrosis of Femoral Head and Has a Positive Correlation with TNF-α and NF-κB P65 - Jing-kun Li; Lei Cheng; Yun-peng Zhao; Ying-jun Guo; Yi Liu; Wei Zhang; Shuai-shuai Wang; Yuan-qiang Zhang; Xin Pan; Lin Nie (Mediators of Inflammation)
ADAMTS-7 has been reported to exaggerate cartilage degeneration and to be associated with TNF-α and NF-κB signaling pathway. In this study we compared the expression of ADAMTS-7, TNF-α, and Phospho-NF-κB in patients with femoral neck fracture (FNF) and osteonecrosis of femoral head (ONFH) at different stages. We found that expression of ADAMTS-7, TNF-α, and Phospho-NF-κB was significantly upregulated in ONFH patients’ articular cartilage and related to the pathogenesis of ONFH. Thus we conclude that ADAMTS-7 level appears to be positively associated with expression of TNF-α and Phospho-NF-κB P65 in cartilage, which may imply its association with cartilage destruction of ONFH.